Statistical probability evaluation of operation time of road transport means - Smičius, Algimantas (Transport, 2003)
One of principal factors hindering the normal process of freight transportation is the insufficient reliability of transport means (especially with the extension of operation time) and their failures caused by various reasons. The article presents the results of processing the flows of failed road transport means. The evaluation of the probability characteristics of failed vehicles is also presented.First Published Online: 19 Dec 2011